Factores de riesgo social relacionados con las infecciones de vías urinarias en mujeres embarazadas que acuden al Centro de Salud de Juan Montalvo - Alarcón Troya, María Cristina (2024)
Urinary infections represent a high risk especially for women of childbearing age, being the stage of pregnancy the highest vulnerability for UTI, with a significant incidence in women exposed to psychosocial risk factors such as economic level, geographic location, access to health services, and marital status, among others. This research was carried out to develop prevention strategies that reduce social risk factors related to urinary tract infections in pregnant women attending the Juan Montalvo Health Center. To this purpose, the methodology applied consisted of the quantitative approach, applied research, descriptive, crosssectional, non-experimental, field and bibliographic design. The population was made up of 75 pregnant patients, the data collection of a questionnaire containing 16 items with response options based on a Likert scale was designed, and the results showed that 52% of the population surveyed had presented UTI during their pregnancy. Among the social risk factors identified, it can be highlighted the lack of access to basic services in women who live in rural areas and have a low income, in addition, a low educational level was found with 48%, and inadequate hygiene practices with 62.70%. Conclusion: from these findings a proposal was designed to prevent and promote health through the implementation of educational workshops, using brochures based on intercultural inclusion, providing the information both in Spanish and Quechua, considering the beliefs, values and cultural practices of these women. It was concluded that psychosocial risk factors can be modified through health promotion and intervention, thus preventing UTIs.